Swedish daylight regulation throughout the 20th century and considerations regarding current assessment methods for residential spaces. (15th March 2021) - Bournas, Iason
Abstract: Daylight availability for buildings has been an integral part of architecture since ancient times, yet for the vast majority of countries, criteria for daylight provision were not normative until the 20th century. This article examines the case of Sweden, where the term "daylight" first appeared in regulations in 1960, and assesses the daylight compliance of multi-dwelling buildings before and after that, in the timespan between 1920 and 2000. Firstly, the study evaluates whether the introduction of daylight criteria improved building performance. Secondly, the two current assessment methods are compared, as a disagreement was expected given that one method is formulated based on the glass-to-floor ratio scheme (GFR-method) while the other on a daylight factor scheme (DFP ). Thirdly, the applicability and limitations of each method are evaluated. Results indicate that dwellings built following the introduction of daylight criteria do not necessarily outperform their predecessors. With respect to assessment methods, it was shown that the GFR-method is of limited applicability due to geometric constraints stipulated in its formulation, primarily due to the violation of the fenestration width condition. When comparing methods, the GFR-method yielded higher compliance compared to DFP, but only marginally. Eventually, the study highlights methodological flaws in the formulation of each criterion. Overall, the work contributes to knowledge supporting the development of daylight requirements for residential spaces. It provides background information suitable for planners and policy makers in their endeavors to define daylight performance criteria. Highlights: Regulations were reviewed since the first mention of the term "daylight" in 1960. The introduction of criteria did not necessarily improve daylight performance. Rooms of the era between 1930 and 1961 have clearly the best performance. The GFR ≥10% criterion is inapplicable in three out of four rooms tested. The current criteria agree in 87% of the cases, due to flaws in their formulations.